2008
DOI: 10.1364/ol.33.001237
|View full text |Cite
|
Sign up to set email alerts
|

Application of radial basis functions to shape description in a dual-element off-axis magnifier

Abstract: We previously demonstrated that radial basis functions may be preferred as a descriptor of free-form shape for a single mirror magnifier when compared to other conventional descriptions such as polynomials [Opt. Express 16, 1583 (2008)]. A key contribution is the application of radial basis functions to describe and optimize the shape of a free-form mirror in a dual-element magnifier with the specific goal of optimizing the pupil size given a 20 degrees field of view. We demonstrate a 12 mm exit pupil, 20 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Cakmakci and Rolland 26 designed a dual-element off-axis near-eye optical magnifier by combining a freeform reflector represented by XY polynomials and a diffractive lens. Furthermore, Cakmakci et al 27 applied the radial basis function, instead of XY polynomials, to characterize the freeform reflector, which could increase the exit pupil diameter from 8 to 12 mm. Cheng et al 7 reported a freeform prism-based head-worn display characterized by XY polynomials, which had the advantages of a fast focal ratio, large field of view, and see-through properties.…”
Section: Applications Of Different Types Of Opticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Cakmakci and Rolland 26 designed a dual-element off-axis near-eye optical magnifier by combining a freeform reflector represented by XY polynomials and a diffractive lens. Furthermore, Cakmakci et al 27 applied the radial basis function, instead of XY polynomials, to characterize the freeform reflector, which could increase the exit pupil diameter from 8 to 12 mm. Cheng et al 7 reported a freeform prism-based head-worn display characterized by XY polynomials, which had the advantages of a fast focal ratio, large field of view, and see-through properties.…”
Section: Applications Of Different Types Of Opticalmentioning
confidence: 99%
“…Thus, the radial basis function is multicentric. Cakmakci et al 27 designed a head-worn display using a Gaussian radial basis function freeform surface, which was integrated into optical design software by applying the "user-defined surface" feature. Moreover, the local feature of the freeform surface can be controlled by the radial basis function.…”
Section: Nonorthogonal Functionsmentioning
confidence: 99%
“…We have been able to extend the field of view from 20 degrees full-field to 25 degrees full-field replacing the x-y polynomial terms of the mirror with RBFs [4]. We also extended the pupil size from 8 mm to 12 mm in the dual-element catadioptric magnifier by using an RBF description on the freeform mirror [5].…”
Section: Application Of Radial Basis Functions To Represent Optical Fmentioning
confidence: 99%
“…In our previous work, we estimated the pupil-size limit of the dual-element magnifier design form to be 12 mm, given a 20°field of view and a 15-mm eye clearance. 15 The main approach of this paper is to describe the free-form mirror using radial basis functions in a dualelement magnifier to establish the field-of-view limit given a >15-mm eye clearance and an 8-mm exit pupil. The design form presented in this paper is an off-axis magnifier that folds the optical axis around a human head while providing the necessary mechanical clearances.…”
Section: Approachmentioning
confidence: 99%